THE ROLE OF THE TEACHER AND THE LEARNING ENVIRONMENT - dos Santos de Carvalho, Juniel; Lopes de Almeida, Tayane; Pereira da Rocha, Diego; Mendes de Oliveira, Zenayre (Revista Gênero e Interdisciplinaridade, 2024)
The present work entitled the role of the teacher and the learning environment, intends to reflect on the role of the teacher in e-learning, presenting the relevance in the innovative perspective in relation to the technological learning environment and the dynamic teacher x technology x students. In search of the consolidation of the theme, it was developed through bibliographical research as a deepening of the subject's knowledge, which is aimed at understanding the importance of the teacher as a mediator for social transformation and as a determinant in the construction of learning. In contemporary times, the role of the teacher is paramount so that we actually have a favorable environment for the development of learning. All the changes promoted by technological innovations must be seen as an anchor for the growth and development of learning and, in this perspective, understand that the role of the teacher will never be replaced, that is, it will always be paramount, since technological resources are here to stay and will always expand the modalities of teaching, thus providing students with diverse knowledge.